Digital Morality and National Values: Pancasila as an Ethical Compass for Technology-Enhanced Counseling in Indonesia - Situmorang, Dominikus David Biondi; Tuaputimain, Hendrik; Muqaffi, Muqaffi; Solehuddin, M. (citeus, 2026)
The very fast development of Artificial Intelligence (AI), Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR) in the last decade have changed the way of mental health practice internationally, including Indonesia. Although these technologies extend reach, deepen therapeutic engagement, and facilitate clinical analysis, they also present serious ethical challenges with respect to privacy, algorithmic bias, depersonalization, and disparity. This integrative review draws on literature from counseling, digital ethics, immersive technologies, and Indonesian philosophical studies to consider how Pancasila can serve as a culturally situated ethical guide for technology-mediated counseling. The results disclose four overarching themes: shifting role of counseling through intelligent and immersive technologies; nascent ethical issues; the salience of Pancasila’s principles to digital morality; and formation of a Pancasila-Based Digital Counseling Ethical Framework (P-DCEF). In this scheme, human dignity, relational integrity, social justice and transparent governance are placed at the heart of ethical digital counseling. It is the reviewer's opinion that embedding technological innovation in national philosophical principles would be imperative to ensuring digital counseling in Indonesia remains humane, just and culturally consistent, bringing a distinct ethical perspective to conversations around mental-health technologies worldwide.